Post‐translational mechanisms are associated with fertility restoration of cytoplasmic male sterility in sugar beet (Beta vulgaris). (18th June 2015) - Kitazaki, Kazuyoshi; Arakawa, Takumi; Matsunaga, Muneyuki; Yui‐Kurino, Rika; Matsuhira, Hiroaki; Mikami, Tetsuo; Kubo, Tomohiko
Summary Genetic conflict between cytoplasmically inherited elements and nuclear genes arising from their different transmission patterns can be seen in cytoplasmic male sterility (CMS), the mitochondrion‐encoded inability to shed functional pollen. CMS is associated with a mitochondrial open reading frame (ORF) that is absent from non‐sterility inducing mitochondria (S‐orf). Nuclear genes that suppress CMS are called restorer‐of‐fertility (Rf) genes. Post‐transcriptional and translational repression of S‐orf mediates the molecular action of Rf that encodes a class of RNA‐binding proteins with pentatricopeptide repeat (PPR) motifs. Besides the PPR‐type of Rfs, there are also non‐PPR Rfs, but the molecular interactions between non‐PPR Rf and S‐orf have not been described. In this study, we investigated the interaction of bvORF20, a non‐PPR Rf from sugar beet (Beta vulgaris), with preSatp6, the S‐orf from sugar beet. Anthers expressing bvORF20 contained a protein that interacted with preSATP6 protein. Analysis of anthers and transgenic calli expressing a FLAG‐tagged bvORF20 suggested the binding of preSATP6 to bvORF20. To see the effect of bvORF20 on preSATP6, which exists as a 250‐kDa protein complex in CMS plants, signal bands of preSATP6 in bvORF20‐expressing and non‐expressing anthers were compared by immunoblotting combined with Blue Native polyacrylamide gel electrophoresis. The signal intensity of the 250‐kDa band decreased significantly, and 200‐ and 150‐kDa bands appeared in bvORF20‐expressing anthers. Transgenic callus expressing bvORF20 also generated the 200‐ and 150‐kDa bands. The 200‐kDa complex is likely to include both preSATP6 and bvORF20. Post‐translational interaction between preSATP6 and bvORF20 appears to alter the higher order structure of preSATP6 that may lead to fertility restoration in sugar beet.